2013
DOI: 10.1121/1.4768795
|View full text |Cite
|
Sign up to set email alerts
|

Measuring subjective response to aircraft noise: The effects of survey context

Abstract: In applied research, noise annoyance is often used as indicator of subjective reaction to aircraft noise in residential areas. The present study aims to show that the meaning which respondents attach to the concept of aircraft noise annoyance is partly a function of survey context. To this purpose a survey is conducted among residents living near Schiphol Airport, the largest airport in the Netherlands. In line with the formulated hypotheses it is shown that different sets of preceding questionnaire items infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Important further sources of variability in the answering behavior in noise surveys are, more generally, context effects. For example, the findings of Kroesen et al [6] support the hypothesis that measuring aircraft noise annoyance in relation to other noise sources creates a context in which people on average express a more extreme aircraft noise annoyance response. The criticism expressed by Brooker [19] about the methodology employed in the Attitudes to Noise from Aviation Sources in England (ANASE)-Study in the UK [20] also suggests that context is an important effect modifier in noise annoyance research.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Important further sources of variability in the answering behavior in noise surveys are, more generally, context effects. For example, the findings of Kroesen et al [6] support the hypothesis that measuring aircraft noise annoyance in relation to other noise sources creates a context in which people on average express a more extreme aircraft noise annoyance response. The criticism expressed by Brooker [19] about the methodology employed in the Attitudes to Noise from Aviation Sources in England (ANASE)-Study in the UK [20] also suggests that context is an important effect modifier in noise annoyance research.…”
Section: Discussionmentioning
confidence: 94%
“…Small changes in design, wording, item positioning, but also survey context or season may introduce variance of annoyance ratings which compromises the reliability and comparability of findings [1,2,3,4]. Owing to this, the research on survey context in the noise annoyance domain [5,6] and research about effects of the annoyance measurement scale employed [7,8] has recently gathered momentum.…”
Section: Introductionmentioning
confidence: 99%
“…Selected studies make use of different study designs, that are laboratory tests [16,[18][19][20][21]24,25,32,34,36,[41][42][43]47] and field campaigns based on socio-acoustic [15,17,22,23,26,28,35,37,39,40,45,46,[48][49][50][51], social surveys [29][30][31]33,38,44], or soundscape assessments [27]. Laboratory studies evaluate testers' response to experimental stimuli in laboratory settings, under controlled conditions.…”
Section: Study Designs Acoustic Measures and Soundscape Data Collecmentioning
confidence: 99%
“…Kroesen et al investigated the impact of the survey context on reported annoyance to aircraft noise [44]. The authors found that items preceding the question about aircraft noise annoyance in the survey design could influence the reported aircraft noise annoyance as well as the correlation trends between annoyance and other dimensions (noise sensitivity, individualism and egalitarianism).…”
Section: Factors Influencing the Acoustic Perception Of Indoor Residementioning
confidence: 99%
“…However, when Miedema and Vos 3 separated the survey data into different curves according to the type of transportation noise (aircraft, traffic, and railway), the aircraft noise yielded a significantly greater percentage of responders highly annoyed for a given day-night level. Although there might be several contributing factors, including the nature of the survey questions themselves, 4 this paper offers a possible explanation for the increased annoyance for aircraft noise as a function of level. At the heart of our explanation is the nature of engines in the legacy aircraft included in the surveys and a perceptual phenomenon known as jet "crackle."…”
Section: Introductionmentioning
confidence: 93%